Karakterisasi Morfologi dan Komponen Hasil Cabai Rawit (Capsicum frutescens L.) Asal Pulau Timor - Maria Afnita Lelang; Syprianus Ceunfin; Adrianus Lelang (Fakultas Pertanian, Universitas Timor, 2019)
Cayenne pepper is one of the germplasm from the island of Timor known as un makaos, un lili, un fua melu or una. Timor cayenne has a unique form that is small in size ranging from 0.5-2 cm in length and a very spicy taste. Small in size between 0.5-2 cm long and very spicy taste. The purpose of this study was to identify the morphological characters and components of the results of cayenne pepper un makaos. The research method is based on the framework of the provisions of UPOV (International Union for the Protection of New Varieties of Plants) and the standards set by IPGRI (International Plant Genetic Resources Institute). The results showed that the characterization of the morphology of cayenne in the island of Timor was identified as having plant habitus with compact branching, cylindrical stem shape, shortening of more than three segments and having green stems. The chili leaves are ovate and green with flat leaf edges and tapered leaf tips. It has a white flower crown with anther blue flowers and an upright flower position on the cayenne tree. Green fruit color before ripe and red when cooking. Has a hornshaped fruit shape (horn shaped) with a blunt fruit tip and has the form of calix enveloping (wrapping). The character of the yield component has a measured average value of 9,47-15,08 g of fruit plant, the average number of fruit plants is 0,73-0,82 g, cayenne has a fruit length of 0,73-0,82 cm and fruit has a diameter of 0,36-0,38 cm.